Time-Resolved Fluorescence Immunochromatography Assay (TRFICA) for Aflatoxin: Aiming at Increasing Strip Method Sensitivity - Li, Hui; Wang, Du; Tang, Xiaoqian; Zhang, Wen; Zhang, Qi; Li, Peiwu (Frontiers in Microbiology, 2020)
Aflatoxin is the most harmful mycotoxin which is ubiquitous in foods and agro-products . Because of its high toxicity, maximum admissible levels of aflatoxins is regulated worldwide and monitoring of their occurrence in several commodities is mandatory for assuring food safety and consumers' health. Considering the strip method is very simple and convenient for users, in order to enhance strip assay’s sensitivity, a lot of time-resolved fluorescence immunochromatography assays (TRFICAs) were developed recently with increasing several times of assay sensitivity compared with traditional gold nanoparticle-based strip assay (GNP-SA). This review briefly describes the newly developed TRFICA for aflatoxin determination, including TRFICA for aflatoxin B1 (AFB1) detection, TRFICA for aflatoxin M1 (AFM1) detection, TRFICA for total aflatoxins (AFB1+B2+G1+G2) detection and the latest identification-nanobody based TRFICA for aflatoxin detection. The application of TRFICA for aflatoxin detection in different agro-products is also concluded in this review. Reasonably, TRFICA has been becoming one of the most important tool for monitoring aflatoxin in foods and agro-products.